Digital Transformation of Toko Susu Bahagia: Implementing an E-Commerce System Using the Waterfall Method - Tiara Ariyanto Putri; Rizky Fadlurohman; Rafi Hilal Zahir; Ihsan Lana Valenza; Muhammad Nasir; Aditya Wicaksono (International Journal Software Engineering and Computer Science (IJSECS), 2025)
The acceleration of information technology advancement necessitates digital system adoption among SMEs to maintain market competitiveness. Toko Susu Bahagia faced operational inefficiencies in inventory management and transaction documentation through manual processes. This research developed a customized e-commerce solution implementing the Waterfall methodology, progressing systematically through requirement analysis, design, implementation, and verification phases. The system architecture utilized PHP (Laravel) framework with MySQL database integration, incorporating essential functionalities: inventory control, order status monitoring, product expiration notifications, and sales analytics. Verification through Black Box Testing yielded a 98% functionality success rate, validating system dependability. Technical obstacles encountered during development included insufficient data validation protocols and limited digital proficiency among users, which were addressed through simplified interface design and enhanced validation mechanisms. The research establishes the practical effectiveness of user-oriented system architecture for small retail enterprises. Operational performance improved through error reduction in manual processes, instantaneous inventory visibility, and expanded market access. The implementation indicates sustained advantages for business growth capacity and technological preparedness. Subsequent research directions may investigate payment gateway integration, language localization capabilities, and responsive design optimization to enhance system versatility.